University students’ use and metalinguistic understanding of code glosses: A cross-linguistic study of students’ L1 Arabic and L2 English argumentative writing - Ahmed, Abdelhamid M. (2025)
This study investigates the use of interactive metadiscourse markers, known as code glosses, in argumentative texts produced by Qatari university students writing in both their L1 Arabic and L2 English. An analysis of 390 texts from the Qatari Corpus of Argumentative Writing identified 1249 instances of code glosses in Arabic and 620 in English. The results indicate that Arabic texts exhibit a higher frequency of both reformulation and exemplification markers compared to their English counterparts. Specifically, the findings suggest that Arabic favours detailed explanations, whereas English is characterised by a preference for concise, illustrative examples. Interviews further support these findings by revealing that exemplification markers effectively engage readers through the use of relatable examples that reinforce evidence and enhance clarity. Additionally, reformulation strategies—such as rephrasing, editing, and restructuring—play a significant role in improving coherence and comprehension. These insights have important implications for curriculum design, suggesting that targeted instruction in the proficient use of code glosses in both L1 Arabic and L2 English could enhance the clarity and overall engagement of students' writing.